Kinerja aparatur pemerintah: Peran gaya kepemimpinan, pengembangan SDM, dan disiplin kerja - Imbar Hadi Wintjoko H; Martaleni Martaleni; Rini Astuti (Nur Science Institute, 2026)
The performance of government employees plays an essential role in ensuring the delivery of effective, responsive, and accountable public services. In practice, differences in leadership approaches, human resource capacity development, and adherence to work rules often create variations in performance across organizational units. This study seeks to explore how these three factors contribute to the performance of government personnel. A quantitative explanatory design was applied in this study. The research respondents were 124 government officials working in 12 sub-districts in Lowokwaru District, Malang City, selected using census techniques. Data were gathered using structured questionnaires with a Likert scale and processed using multiple regression techniques. The results indicate that leadership practices, human resource development efforts, and work discipline are all positively associated with employee performance. Among them, human resource development emerges as the most influential factor. Collectively, these variables provide a substantial explanation of performance variation, indicating a strong model fit. In summary, enhancing government employees' performance requires a balanced effort to strengthen leadership quality, continuously develop employee competencies, and maintain consistent work discipline.